“L’immortel Chancelier d’Angleterre” : Francis Bacon, Memory and Method - Andrew Hiscock (Revue LISA)
This article focuses upon the status and functions of memory in the natural philosophy of Francis Bacon (1561-1626). The first phase of the discussion reviews the intellectual legacies from antiquity and the medieval centuries which continued to shape learning at the close of the 16th century across Europe. Subsequently, the article considers the ways in which Bacon evaluated the influence of Aristotelian thinking on the educational practices of his time. An investigation of his writings dating from the early decades of the 17th century demonstrates how Bacon saw the age’s abiding fascination with memory as a significant obstacle to the progress of scientific thinking in Europe. In its closing phases, this article examines how the role of writing (rather than that of memory) is foregrounded in Bacon’s writing; and, finally, the article briefly examines the reception of Bacon and his thinking in the 18th and 19th centuries.